The Role of Nurses in Preventing Hip Arthroplasty Complications in the Postoperative Period - Gurskienė, Olga (Slauga. Mokslas ir praktika, 2023)
Abstract. Hip joint replacement is one of the most popular operations in orthopedics. During the surgical procedure, the hip joint is replaced with a prosthesis, therefore, after this operation, in order to avoid complications, the role of nurses is very important, which must be reflected in professionalism and responsibility. It should be noted that nurses must not only perform general care, but also involve the patient in the nursing process, i.e. discuss the care plan, carry out training so that the patient feels safe and self-confident.The aim of the research based on a review of the scientific literature, to analyze the role of nurses in order to prevent hip arthroplasty complications in the postoperative period.Research methods. The systematic scientific literature review was prepared using the PRISMA (Perferred Reporting Item for Systematic Review and MetaAnalyses) method. Scientific articles were searched in the three main electronic databases PubMed, Google Scholar, Ceeol in Lithuanian and English, in the period 2011– 2021. To search for scientific publications, use terms that correspond to the purpose of the study (hip joint replacement, postoperative complications, nursing, the role of the nurse), where a total of 14 (n = 14) scientific articles were selected and included.
Keywords: hip joint re-placement; postoperative complications; nursing; the role of the nurse